EXPERIENCE WITH THE UNITED STATES DEPARTMENT OF AGRICULTURE (USDA) CENTER FOR GRAIN AND ANIMAL HEALTH RESEARCH (CGAHR) ARTHROPOD-BORNE ANIMAL DISEASES RESEARCH UNIT (ABADRU: CONSIDERING RIFT VALLEY FEVER AND OCCUPATIONAL BIOSAFETY AND HAZARD PRACTICES - Roof, Clinton (My University, 2012)
The Master of Public Health (MPH) capstone experience results in numerous personal and academic gains. Through my MPH capstone experience, I was able to utilize knowledge gained from previously related classes. I gained exposure and understanding of the risks and hazards of zoonotic disease research, especially as it relates to attenuated Rift Valley fever virus (MP-12) in a Biosafety Level (BSL)-2 Research Facility. I was also able to achieve an understanding of what procedures should be in place to protect the occupational safety of workers in the laboratory or research setting. Finally, in a Frontier trip to the United States-Mexico Border Port of Entry in Santa Teresa, New Mexico, I was able to observe the real life activities, issues, and actions, which occur on a daily basis to protect and defend this nation’s public health and food supply. The risk of foreign animal or zoonotic disease outbreaks are high today and may be rising. The reasons involved include increased international trade and travel, population growth, the changing patterns of human-animal contact, an increased demand for animal protein, increased wealth, environmental changes and human encroachment of farm land and previously undisturbed wildlife habitat. Infectious disease outbreaks can cause human suffering/death and substantial economic losses to the agricultural sectors resulting in disrupted agricultural commodity markets. Zoonotic diseases such as those caused by Rift Valley fever virus (RVFV) can spread from humans to animals and vice-versa, raising an additional dimension of vulnerability to human health. Rift Valley fever virus is not considered an immediate risk to the continental United States; however, it is considered a possible threat and, if established, could result in similar consequences as West Nile Virus (WNV) in 1999. Its socioeconomic impact and significant effect on human health and livestock could resemble the economically crippling effect seen in countries, such as those in Africa. This impact is seen in the form of stressed health care services, decreased animal reproduction, and financial loss due to human and animal morbidity and mortality, and national as well as international trade restrictions. Through the understanding of RVFV’s global importance and the application of zoonotic agent laboratory research, I was able to produce two PowerPoint presentations, which will be useful as training exercises for new laboratory workers starting with the Arthropod-Borne Animal Disease Research Unit (ABADRU). Additionally, I was able to participate in the preliminary occupational risk evaluation of an intradermal needle-free injection device, for the potential use in future ABADRU work.
Keywords: Rift Valley Fever; USDA; Occupational biosafety; Occupational hazards; Public Health (0573)